Error treatment revisited: Examining learners' and instructors' preferences in grammar classroom / Kamisah Hj Ariffin and Misyana Susanti Husin - Hj Ariffin, Kamisah; Husin, Misyana Susanti (Universiti Teknologi MARA Cawangan Pahang, 2009)
Learners make mistakes or errors in the process of learning. Error treatment is very important as learners will get information on their performance and clear understanding of what should have been learned or acquired. This is because the treatment of errors can influence learners' motivational learning behavior : However, what kind of treatment can best benefit the learners? This paper, thus, investigates both the learners' and instructors' preferences towards error treatment in English as a Second Language (ESL) grammar classroom as both parties have intuitive knowledge about the kind of treatment that can benefit learning the most. The interview and survey data reveal that both the learners and instructors have different preferences in the treatment of errors. The findings reveal that students preferred explicit corrections the most while the instructors preferred the providing clues for sell-repair method of treatment. Pedagogically, the findings point out that instructors have to employ the appropriate measure for error treatment in the classroom for the benefit of learning.